2018
DOI: 10.1002/btpr.2757
|View full text |Cite
|
Sign up to set email alerts
|

A protocol to transfer a fed‐batch platform process into semi‐perfusion mode: The benefit of automated small‐scale bioreactors compared to shake flasks as scale‐down model

Abstract: in Wiley Online Library (wileyonlinelibrary.com) Continuous processes such as perfusion processes can offer advantages compared to fed-batch or batch processes in bio-processing: improved product quality (e.g. for labile products), increased product yield, and cost savings. In this work, a semi-perfusion process was established in shake flasks and transferred to an automated small-scale bioreactor by daily media exchange via centrifugation based on an existing fed-batch process platform. At first the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…The fed‐batch shake flasks studies have shown tris as a lever for modulating high mannose glycans similarly to kifunensine and DMJ. The shake flask scale down model has limitations due to lack of pH and DO control, which may impact VCD and viability 51,52 . To confirm the impact of the inhibitors in a process scalable to a 15,000 L bioreactor, the novel inhibitors were evaluated in a 5 L bioreactor scale down model 35,53 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fed‐batch shake flasks studies have shown tris as a lever for modulating high mannose glycans similarly to kifunensine and DMJ. The shake flask scale down model has limitations due to lack of pH and DO control, which may impact VCD and viability 51,52 . To confirm the impact of the inhibitors in a process scalable to a 15,000 L bioreactor, the novel inhibitors were evaluated in a 5 L bioreactor scale down model 35,53 …”
Section: Resultsmentioning
confidence: 99%
“…The shake flask scale down model has limitations due to lack of pH and DO control, which may impact VCD and viability. 51,52 To confirm the impact of the inhibitors in a process scalable to a 15,000 L bioreactor, the novel inhibitors were evaluated in a 5 L bioreactor scale down model. 35,53 3.3 | Confirmation of inhibitor effects in bioreactor scale down model Addition of 10 mM tris to CL1 had no significant impact on VCD, viability, or titer and was comparable to the control process ( Figure 7).…”
Section: Dose-dependent Response Of Novel Inhibitormentioning
confidence: 99%
“…The major drawback of the ST system, with respect to the bench‐scale reactors, is the lack of pH and DO control, as well as the different type of agitation. The most recent study of Janoschek et al () uses an automated and well controlled bioreactor system and appears to reproduce the bioreactor conditions in a much better way. Additionally, proper technologies, such as flux balance analysis and metabolic flux analysis, could be used to better understand the metabolic differences observed in the ST and the bench‐scale system.…”
Section: Resultsmentioning
confidence: 99%
“…The system is operated at 15 ml and shows comparable process performance to large scale reactors (Goletz, Stahn, & Kreye, ). Most recently, Janoschek, Schulze, Zijlstra, Greller, and Matuszczyk () presented a similar semi‐continuous approach in the ambr® 15 system, but instead applied centrifugation to separate cells from the culture medium, and therefore strongly reduced the time without bioreactor control compared with the sedimentation method. The approach allows the control of pH, DO, and agitation during perfusion culture and appears to be a very close representation of a fully automated perfusion reactor with cell retention system (Janoschek et al, ), but still needs further validation with bench‐scale systems.…”
Section: Introductionmentioning
confidence: 99%
“…The use of polymer-based controlled-release fed-batch microtiter plates during preculture was theoretically studied and tested with an E. coli clone bank containing 32 strains (Keil et al, 2019). The suitability of an automated smallscale bioreactor (ambr 15 with 48 wells) as a small-scale model was confirmed using a perfusion process (Janoschek et al, 2019). In another study, it was reported that an automated microbioreactor system (ambr15) can be utilized to scale down the perfusion process using cell sedimentation (as the cell retention method).…”
Section: High-throughput Cultivation Systemsmentioning
confidence: 99%